Cytotoxic styryl-lactones from the leaves and twigs of Polyalthia crassa - Patoomratana Tuchinda (2018)
Four new styryl-lactones, crassalactones A-D (1-4), were isolated from a cytotoxic ethyl acetate-soluble extract of the leaves and twigs of Polyalthia crassa, together with seven known compounds, (+)-3-acetylaltholactone, (+)-altholactone, aristolactam All, cinnamic acid, (+)-goniofufurone, (+)-goniopypyrone, and (+)-howiinol A. Their structures were determined on the basis of spectroscopic methods. The absolute configuration of 1-3 was established by chemical conversions. Single-crystal X-ray analysis and the Mosher ester method were used to confirm the absolute stereochemistry of 4. Cytotoxic evaluation against several mammalian cancer cell lines was performed on all new isolates, aristolactam AII, and the modified (+)-tricinnamate derivative 11 obtained from 1. © 2006 American Chemical Society and American Society of Pharmacognosy.